Konsep Belajar Dalam Kaitan Materi Pengembangan Kognisi - Nanik Ernawati (https://ejournal.insuriponorogo.ac.id/, 2025)
This paper explores the pivotal role of cognitive learning in the development of key academic skills across various disciplines, including reading, writing, mathematics, science, and social studies. Cognitive learning is defined as an active process involving the acquisition, processing, storage, and application of knowledge, with an emphasis on critical cognitive functions such as memory, critical thinking, information processing, perception, and decision-making. Through a thorough review of relevant literature, the study highlights how cognitive learning facilitates students' understanding of fundamental concepts, from phonemic awareness and text comprehension in reading to logical reasoning and problem-solving in mathematics and science. It also underscores the importance of cognitive learning in developing the ability to analyze social structures and historical contexts within social studies. The research advocates for the integration of cognitive learning strategies in educational practices, emphasizing techniques such as modeling, repetitive practice, constructive feedback, and open-ended questioning to enhance cognitive engagement and promote higher-order thinking. Additionally, the study calls for a holistic approach to education that incorporates cognitive learning with other dimensions of learning, ultimately aiming to improve students' academic performance and their ability to apply knowledge in practical, real-world contexts.